Galaxy-scale outflows driven by active galactic nuclei - DeBuhr, Jackson; Quataert, Eliot; Ma, Chung-Pei (Monthly notices of the Royal Astronomical Society, 2012)
We present hydrodynamical simulations of major mergers of galaxies and study the effects of winds produced by active galactic nuclei (AGN) on interstellar gas in the AGN's host galaxy. We consider winds with initial velocities ∼10 000 km s−1 and an initial momentum (energy) flux of ∼τw L/c (∼ 0.01  τw L), with . The AGN wind sweeps up and shock heats the surrounding interstellar gas, leading to a galaxy-scale outflow with velocities ∼1000 km s−1, peak mass outflow rates comparable to the star formation rate and a total ejected gas mass of ∼3 × 109 M⊙. Large momentum fluxes, τw≳ 3, are required for the AGN-driven galactic outflow to suppress star formation and accretion in the black hole's host galaxy. Less powerful AGN winds (τw≲ 3) still produce a modest galaxy-scale outflow, but the outflow has little global effect on the ambient interstellar gas. We argue that this mechanism of AGN feedback can plausibly produce the high-velocity outflows observed in post-starburst galaxies and the massive molecular and atomic outflows observed in local ultraluminous infrared galaxies. Moreover, the outflows from local ultraluminous infrared galaxies are inferred to have τw∼ 10, comparable to what we find is required for AGN winds to regulate the growth of black holes and set the M BH - σ relation. We conclude by discussing theoretical mechanisms that can lead to AGN wind mass loading and momentum/energy fluxes large enough to have a significant impact on galaxy formation.